2019
DOI: 10.1016/j.nicl.2019.101686
|View full text |Cite
|
Sign up to set email alerts
|

Patients with sickle-cell disease exhibit greater functional connectivity and centrality in the locus coeruleus compared to anemic controls

Abstract: HighlightsPatients with sickle-cell disease (SCD) have greater resting-state functional connectivity between the locus coeruleus (LC) and dorsolateral prefrontal cortex (dlPFC).Patients with SCD have greater resting state centrality of the LCSCD patients with chronic pain exhibited even greater functional connectivity between the LC and dlPFC.This study supports hyper-connectivity between the LC and PFC is a potential chronic pain generator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 86 publications
(108 reference statements)
2
11
0
Order By: Relevance
“…17,24 Additionally, Bhatt et al found differences in connectivity of the locus coeruleus, a region involved in pain processing, in SCD. 23 We also found decreased connectivity within the auditory network, which is supported by mounting evidence that patients with SCD suffer hearing loss. Between 13% and 62% of tested patients are affected by hearing loss, with 6.6% to 13% having a component of sensorineural hearing loss.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…17,24 Additionally, Bhatt et al found differences in connectivity of the locus coeruleus, a region involved in pain processing, in SCD. 23 We also found decreased connectivity within the auditory network, which is supported by mounting evidence that patients with SCD suffer hearing loss. Between 13% and 62% of tested patients are affected by hearing loss, with 6.6% to 13% having a component of sensorineural hearing loss.…”
Section: Discussionsupporting
confidence: 77%
“…Five additional studies compared fcMRI between controls and adults with SCD. 19,20,[22][23][24] Interpretation and generalization of these investigations is challenging due to small sample sizes, inclusion of all SCD genotypes and/or chronically transfused participants with SCD, and a variety of analytic techniques. Using a graphlasso based test, Coloigner et al did not find connectivity differences in the majority of patients with SCD compared with controls, however, these results are challenging to reconcile with our data as 55% of the SCD cohort in this study was receiving chronic transfusion therapy or had hemoglobin SC disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations